Electrocatalytic SiC Nanoparticles/PEDOT:PSS Composite Thin Films as the Counter Electrodes of Dye‐Sensitized Solar Cells. Issue 6 (5th June 2014) - Tsai, Yu‐Lin; Li, Chun‐Ting; Huang, Tzu‐Yen; Lee, Chi‐Ta; Lin, Chen‐Yang; Chu, Chih‐Wei; Vittal, R.; Ho, Kuo‐Chuan
Abstract The front cover artwork is provided by Professor Kuo‐Chuan Ho's Electro‐optical Materials Lab at the Department of Chemical Engineering, National Taiwan University. The image shows a Pt‐free composite of silicon carbide nanoparticles/poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (SiC‐NPs/PEDOT:PSS) as the counter electrode in a dye‐sensitized solar cell (DSSC), which has a good electrocatalytic ability for I‐/I3 ‐ . Read the full text of the article at 10.1002/celc.201300242.